2022
DOI: 10.1007/s12144-022-03421-3
|View full text |Cite
|
Sign up to set email alerts
|

Could mindfulness diminish mental health disorders? The serial mediating role of self-compassion and psychological well-being

Abstract: The COVID-19 pandemic clearly has various detrimental psychological effects on people’s mental health, emphasizing the importance of mindfulness in overcoming such repercussions. This is in line with the growing number of studies that have been conducted to assess the effects of mindfulness in diverse settings. However, the role of mindfulness in reducing mental health issues among university students has received little attention. Therefore, the current work seeks to investigate how mindfulness could reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…However, mindfulness was indirectly associated with anxiety via intolerance of uncertainty, experiential avoidance, and positive affect, and indirectly associated with depression via self-compassion, experiential avoidance, and positive affect. This is consistent with studies demonstrating that intolerance of uncertainty, self-compassion, and experiential avoidance mediate the effects of mindfulness on depression and anxiety outcomes (Kraemer et al, 2016;McCluskey et al, 2022;Tran et al, 2022). Notably, to our knowledge, this is the first study to point to such a role for positive affect.…”
Section: Variables Associated With Depression and Anxietysupporting
confidence: 91%
“…However, mindfulness was indirectly associated with anxiety via intolerance of uncertainty, experiential avoidance, and positive affect, and indirectly associated with depression via self-compassion, experiential avoidance, and positive affect. This is consistent with studies demonstrating that intolerance of uncertainty, self-compassion, and experiential avoidance mediate the effects of mindfulness on depression and anxiety outcomes (Kraemer et al, 2016;McCluskey et al, 2022;Tran et al, 2022). Notably, to our knowledge, this is the first study to point to such a role for positive affect.…”
Section: Variables Associated With Depression and Anxietysupporting
confidence: 91%
“…Mindfulness can increase positive qualities such as awareness, insight, wisdom, compassion, and serenity ( Kabat-Zinn, 2000 ; Goldstein, 2002 ), which protects mental health. Therefore, college students should be cared for and supported to overcome the COVID-19 crisis by focusing on their mindfulness ( Tran et al, 2022 ). Some scholars have argued that mindfulness is a trait that improves with practice or experience.…”
Section: Introductionmentioning
confidence: 99%
“…It has six dimensions measured on a 5-point Likert scale ranging from 1 (almost never) to 5 (almost always). The scale adapted to Vietnamese students (Nguyen et al, 2020 ; Tran et al, 2022a , 2022b ) has good reliability and validity. Our Confirmatory Factor Analysis (CFA) showed that the measurement model achieved a satisfactory fit at X 2 / df = 3.07 ( p < 0.001 ); CFI = 0.90; TLI = 0.90; RMSEA = 0.06, and 90% CI [0.06,0.07], Cronbach’s alpha = 0.90.…”
Section: Methodsmentioning
confidence: 99%